قيمة الحنين في شعر محمود درويش وكياهي الحاج مصطفى بسري: دراسة في الادب المقارن | The Value of Longing in the Poetry of Mahmoud Darwish and K.H. Mustofa Bisri: A Comparative Literature Study - Adnan Halim Husni; Yeni Ratna Yuningsih; Siti Sa’adah; Merry Choirani; Khairul Azmi; R Yudha Alamsyah (IAIN Madura, 2026)
This article examines the value of longing in the poems “Ilā Ummī” by Mahmud Darwish and “Ibu” by K.H. Mustofa Bisri through a comparative literature approach. The study aims to explain how longing is constructed differently in two cultural contexts, Arab-Palestinian and Indonesian. The method employed is qualitative with a close reading technique, grounded in Raymond Williams’s Cultural Materialism approach, which views literary works as cultural practices. The analysis focuses on longing as a value that shapes human relations with the self, with others, and with the origins of life. The findings show that in Darwish’s poetry, longing functions as a cultural response to experiences of alienation and loss, whereas in Gus Mus’s poetry, longing serves as an ethical reflection on sustained relationships. These findings confirm that longing is not merely a personal emotion, but a cultural value shaped by the social and historical conditions of the poet. This study contributes to comparative literature by positioning longing as an analytical category based on cultural context.